WORLD PREHISTORY a brief introduction. - Fagan, Brian M.; Durrani, Nadia (NEW YORK : ROUTLEDGE, 2019)
This popular introductory textbook provides an overview of more than 3 million years of human prehistory. Written in an accessible and jargon-free style, this engaging volume tells the story of humanity from our beginnings in tropical Africa up to the advent of the world's first urban civilizations. A truly global account, World Prehistory surveys the latest advances in the study of human origins and describes the great diaspora of modern humans in the millennia that followed as they settled Europe, Asia, and the Americas. Later chapters consider seminal milestones in prehistory: the origins of food production, the colonization of the offshore Pacific, and the development of the first more complex human societies based, for the most part, on agriculture and stock raising. Finally, Fagan and Durrani examine the prevailing theories regarding early state-organized societies and the often flamboyant, usually volatile, preindustrial civilizations that developed in the Old World and the Americas. Fully updated to reflect new research, controversies, and theoretical debates, this unique book remains an ideal resource for the beginner first approaching archaeology. Drawing on the experience of two established writers in the field, World Prehistory is a respected classic that acquaints students with the fascinations of human prehistory.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Archaeology; Prehistoric peoples; Anthropology, Prehistoric; Human evolution; Antiquities, Prehistoric